Shock tubes : proceedings of the seventh International Shock Tube Symposium held at University of Toronto, Toronto, Canada, 23-25 June 1969 - Glass, I. I., 1918- (University of Toronto Press, 1970)
This volume contains the proceedings of a symposium held at the University of Toronto in June 1969. The symposium consisted of six sessions; each containing an invited paper, followed by six contributed papers reporting on recent, relevant research and development. The topics are: a review of research problems in basic shock tube flows and the possibilities for the shock tube in the future; driving techniques; explosive drivers; theoretical and experimental research in electromagnetic shock tubes; chemical kinetics and spectroscopy; and a review of shock tube diagnostics, instrumentation and fundamental data as well as the measurement of physical quantities.